Comparative study of NGOs towards disaster risk reduction in Nigeria - Gabarin Umar, Abubakar; Ali, Maimunah (Associated Asia Research Foundation (AARF), 2018)
The aim of this paper is to explore some comparative advantages of training indigenous groups towards disaster risk reduction. Non-Governmental Organizations (NGOs) are nonprofit organizations that have been recognized based on their efforts towards uplifting the poor, marginalized, unprivileged, underprivileged, impoverished and downtrodden groups. Based on related works, it is well known factor that on the average, a disaster occurs somewhere else in Nigeria’s each day and the Non-Governmental Organizations (NGOs) are usually the first or second agents to respond to humanitarian crisis, political, breakdown of the law and order. But it is unfortunate that even the NGOs suffered the same fate with the victims due to inadequate trainings on disaster risk reduction technics in Nigeria as a result of growing number of factors militating against them. The study followed a qualitative research strategy to conduct interviews with pre-tested interviews as key data collection instrument which was used in eliciting responses from10 heads of NGOs randomly selected from the North-Eastern Nigeria to seek information about the main NGOs missions in the region. The paper uses comparative analysis between Nigeria versus Malaysia to evaluate what is working well and what need to be corrected as both countries are party to world conference were global best framework on disaster risk reduction was developed at Sendai, Japan in 2015.